2020
DOI: 10.1101/2020.03.26.20044057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Paraclinical Characteristics of COVID-19 patients: A systematic review and meta-analysis

Abstract: Introduction:Recently, a new strain of coronaviruses, which originated from Wuhan City, Hubei Province, China has been identified. According to the high prevalence of new coronavirus, further investigation on the clinical and paraclinical features of this disease seems essential. Hence, we carried out this systematic review and meta-analysis to figure out the unknown features. Methods:This study was performed using databases of Web of Science, Scopus and PubMed.We considered English cross-sectional and case-se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…Numerous hospital case series and observational studies have described the clinical characteristics of patients in symptomatic phases; headache is recorded among these symptoms. Meta‐analysis of these studies shows that headache is reported in 6%‐15% of patients 1‐8 . All these data are from studies conducted in China; however, preliminary data from our setting suggest that approximately 60% of patients with COVID‐19 presented with headache 8 …”
Section: Introductionmentioning
confidence: 81%
“…Numerous hospital case series and observational studies have described the clinical characteristics of patients in symptomatic phases; headache is recorded among these symptoms. Meta‐analysis of these studies shows that headache is reported in 6%‐15% of patients 1‐8 . All these data are from studies conducted in China; however, preliminary data from our setting suggest that approximately 60% of patients with COVID‐19 presented with headache 8 …”
Section: Introductionmentioning
confidence: 81%
“…SARS-CoV-2 generally begins as a flu-like syndrome explaining the high prevalence of headache, myalgia and dizziness that likely reflect systemic inflammation more than a direct neurological involvement, as their frequency correlates with the severity of the pulmonary involvement ( Heydari et al., 2020 ). As shown in observational studies published during first weeks after the spread of the pandemic ( Wang et al., 2020 ; Huang et al., 2020 ; Zhou et al., 2020 ; Chen et al., 2020 ), the most frequent neurological-like symptoms were myalgia (11–44%), followed by fatigue (23–69.9%) and headache (6.5–8%).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, these reviews (published until April 23, 2020) corroborate the original descriptions: only fever and cough are present in more than half of the patients, with fatigue closely following (30.4-42.0%). [34][35][36][37] Abnormal findings on chest imaging compatible with COVID-19 were reported for 88.2 to 96.6% of patients. According to a recent summary, most patients present more than one symptom on admission, but the combination of fever, cough, and shortness of breath is rare.…”
Section: A Kaleidoscopic Diseasementioning
confidence: 99%